The Effectiveness of Modified Mediterranean and Traditional Persian Diets in Fatigue and Depressive Severity in People with Multiple Sclerosis: A Randomized Controlled Clinical Trial - Mohammad Hossein Sharifi; Maryam Poursadeghfard; Maryam Afshari; Zahra Alizadeh; Mohammad Vatanpour; Mitra Soltani; Hossein Molavi Vardanjani; Amir Mohammad Jaladat; Majid Nimrouzi (Iranian Journal of Medical Sciences)
Background: Research into managing depression and fatigue, two typical symptoms of multiple sclerosis (MS), is constantly expanding. This study aimed to assess the efficacy of the modified Mediterranean (MED) diet or the Traditional Persian (TP) diet in terms of fatigue and depression severity in patients with MS.Methods: In this single-center, single-blind, randomized clinical trial, 90 patients were enrolled. The patients were randomly assigned to either the MED or TP diet intervention and control groups for two months between July 2022 and February 2023, in Shiraz, Iran. The Krupp Questionnaire for Fatigue Severity Scale and the Beck Depression questionnaire were used. The Chi square test, Kruskal-Wallis test, One-way ANOVA, and backward elimination technique were employed. STATA statistical software (version 17) was utilized for data analysis. P≤0.05 was considered statistically significant.Results: The mean age of 90 participants was 35.64±9.12, and 82.2% were women. The analysis revealed a negative correlation between fatigue severity and MED diet intervention (-4.17 [-8.18-0.16]; P=0.04). However, there was no association between fatigue severity and TP diet intervention (-3.82 [-7.96, 0.32]; P=0.07). The analysis showed that there was a statistically significant relationship between lower depression scores and TP diet intervention (-2.89 [-5.59, -0.19]; P=0.03). However, there was no association between depression scores and MED diet intervention (P=0.22). Lower depression score was also associated with older age and higher socioeconomic status (P=0.002 and P=0.006). It was also shown that longer duration of disease (P=0.05) and higher fatigue severity (P=0.001) were associated with higher depression scores. Conclusion: Adhering to the MED diet could reduce fatigue scores in MS patients while having no effect on the depression score. In contrast, adhering to the TP diet recommendation could reduce depression scores without affecting fatigue scores in MS patients.Trial registration number: IRCT20181113041641N1.